The Implementation of Flipped Classroom Learning Model to Improve Vocabulary Mastery at the Tenth Grade Students’ of SMA Negeri 14 Bone: Penelitian - A. Rezky Amelia A. Bohang; Muhammad Jafar; Dian Riani Said (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this study was to determine whether the application of a multimedia-based flipped learning model can improve students' vocabulary comprehension and also to measure student activity when they are active in class during English learning activities using research instruments in the form of tests and observation sheets. Classroom Action Research uses 2 cycles, using the Kurt Lewins model and the subject of the study is class X.4 at SMA Negeri 14 Bone. The results of this study were said to be successful by showing an increase in the average value of students from the pre-test to cycle 1, which was 30.3% and an increase from the pre-test to cycle 2, which was 58.1%. Then from the results of the observation, it can be concluded that the application of the multimedia-based flipped classroom learning model can improve the vocabulary comprehension skills of class X.4 students of SMA Negeri 14 Bone.